Pengaruh Good Corporate Governance Terhadap Nilai Perusahaan dengan Ukuran Perusahaan Sebagai Variabel Moderasi pada Perusahaan yang Terdaftar di Bursa Efek Indonesia Periode 2017-2019 - Ryanti Devita; Robinhot Gultom; Rintan Saragih (Jurnal Ilmu Manajemen METHONOMIX, 2024)
This study aims to determine the effect of the Board of Directors, Independent Commissioners, Audit Committee on Firm Value with Firm Size as a Moderating Variable in plantation companies listed on the Indonesia Stock Exchange for the 2017-2019 period. The variables used in this study consisted of Good Corporate Governance proxied by the Board of Directors (X1), Independent Commissioners (X2), Audit Committee (X3), Company Value as proxied by Tobin's Q and Company Size (Z) as Moderating Variables. The sample in this study consisted of 13 companies with financial statements from 2017 – 2019. Data analysis used multiple linear regression analysis. The results showed that the Board of Directors, Independent Commissioner, Audit Committee simultaneously had no effect on firm value. Partially, the Board of Directors, the Audit Committee have no effect on the value of the company, while the Independent Commissioner has an effect on the value of the company. Meanwhile, firm size is not able to moderate the relationship between the board of directors and the audit committee with firm value and firm size is able to moderate the relationship between independent commissioners and firm value.